Shoot multiplication via elongated stem node culture under darkness: a novel method in micropropagation of Paphiopedilum villosum - Huy, Nguyen Phuc; Tinh, Dang Thi; Luan, Vu Quoc; Tung, Hoang Thanh; Hien, Vu Thi; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2018)
Paphiopedilum villosum is a beautiful orchid species and has high value in trade; however, this is one of the most difficult to propagate orchids. So far, there has been very little publication on micropropagation. In this study, the effects of plant growth regulators on shoot regeneration from stem node culture of elongated P. villosum shoots in the darkness were investigated. Shoots (1.5 cm) were elongated and produced individual stem nodes under darkness condition for 3 months. Stem nodes were cultured on SH medium and supplemented with individually BA, KIN or TDZ to investigate shoot regeneration. The shoot multiplication rate was also recorded in this study. The highest stem node was observed in the dark with 5.25 cm in the height and the number of stem nodes were 3 stem nodes/shoot. The isolated stem node was cultured on SH medium supplemented with 30 g/L sucrose, 8 g/L agar, 1 g/L charcoal and different concentrations of BA, KIN, TDZ. The results observed after 3 months showed that the best shoot regeneration rate (85%) and highest shoot multiplication coefficient (6.6 shoots/stem node) was obtained when shoots derived from stem node were cultured on SH medium supplemented with 0.5 mg/L TDZ, 30 g/L sucrose, 8 g/L agar and 1 g/L charcoal. Those shoots obtained in the above treatments were subcultured on MS medium supplemented with 0.3 mg/L NAA for rooting and gave the highest number of roots (6.6 roots/shoot) after 1 month; and these plantlets were acclimatized in Taiwan sphagnum moss and transferred into greenhouse with the best survival rate (100%) after 3 months.